A multilayer network model for studying the impact of non-pharmaceutical interventions implemented in response to COVID-19 - Chen, Peiyu; Guo, Xudong; Jiao, Zengtao; Liang, Shihao; Li, Linfeng; Yan, Jun; Huang, Yadong; Liu, Yi; Fan, Wenhui (Frontiers in Physics, 2022)
Non-pharmaceutical interventions (NPIs) are essential for effective prevention and control of the COVID-19 pandemic. However, the scenes for disease transmission are complicated and varied, and it remains unclear how real-world networks respond to the changes in NPIs. Here, we propose a multi-layer network combining structurally fixed social contact networks with a time-varying mobility network, select the COVID-19 outbreak in two metropolitans in China as cases study, and assess the effectiveness of NPIs. Human mobility both in relatively fixed places and in urban commuting is considered. The enclosed places are simulated by three different types of social contact networks while urban commuting is represented by a time-varying commute network. We provide a composite framework that captures the heterogeneity and time variation of the real world and enables to simulate large populations with low computational costs. We give out a thorough evaluation of the effectiveness of NPIs (i. e. work from home, school closure, close-off management, public transit limitation, quarantine, and mask use) under certain vaccine coverage varying with implementation timing and intensity. Our results highlight the strong correlation between the NPI pattern and the epidemic mitigation effect and suggest important operation strategies for epidemic control.